2012
DOI: 10.1007/s10995-012-1179-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with a Patient-Centered Medical Home Among Children with Behavioral Health Conditions

Abstract: At some point in their lives, nearly one-half of all American children will have a behavioral health condition. Many will not receive the care they need from a fragmented health delivery system. The patient-centered medical home is a promising model to improve their care; however, little evidence exists. Our study aim was to examine the association between several behavioral health indicators and having a patient-centered medical home. 91,642 children's parents or guardians completed the 2007 National Survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Regression models included socio-demographic variables previously associated with differences in health status, health care quality, or autism severity, 14,30,31 including child age, gender, race/ethnicity/language, household income relative to federal poverty level (FPL), insurance type, and geographic region. We also examined the frequency of the most common health conditions among all CSHCN in all three groups of interest, as well as number of total health conditions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Regression models included socio-demographic variables previously associated with differences in health status, health care quality, or autism severity, 14,30,31 including child age, gender, race/ethnicity/language, household income relative to federal poverty level (FPL), insurance type, and geographic region. We also examined the frequency of the most common health conditions among all CSHCN in all three groups of interest, as well as number of total health conditions (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous studies, child and maternal risks were identified by the following four variables: (1) child health status (fair/poor or excellent/very good/good), (2) maternal general health (fair/poor or excellent/very good/good), (3) maternal mental/emotional health (fair/ poor or excellent/very good/good) and (4) maternal education level (less than high school or high school or higher) [7][8][9]19]. It is important to note that child health status could be considered either a risk factor (i.e., predictor) or outcome of having a medical home.…”
Section: Measures and Analysismentioning
confidence: 99%
“…The current study similarly examines the effects of negative events that children experience but in relation to their clinical environment. Whereas previous studies show some children have disproportional rates of having a medical home, [6][7][8][9][10]19] our study will examine the relation family and environmental risks, including ACEs, having a medical home. This will add an important piece to the literature so that future research can identify whether having a medical home may be a mediating factor between experiencing negative events and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another set of issues arises for individuals who receive services from various providers and agencies, for example, child psychiatrists, social workers, educators, psychologists, speech pathologists, behavior specialists, and so on. The primary care provider has an increasingly important role in care coordination and provision of a "medical home" (Hyman & Johnson, 2012;Knapp et al, 2013). This book is written to address the needs of primary care providers for what we hope is an accessible and straightforward guide to medical care for individuals with autism, Asperger's, and the broader autism spectrum group of conditions.…”
mentioning
confidence: 99%